Molecular detection of bovine Noroviruses in Argentinean dairy calves : circulation of a tentative new genotype - Ferragut, Fátima (2016)
Bovine noroviruses are enteric pathogens detected in fecal samples of both diarrheic and non-diarrheic calves from several countries worldwide. However, epidemiological information regarding bovine noroviruses is still lacking for many important cattle producing countries from South America. In this study, three bovine norovirus genogroup III sequences were determined by conventional RT-PCR and Sanger sequencing in feces from diarrheic dairy calves from Argentina (B4836, B4848, and B4881, all collected in 2012). Phylogenetic studies based on a partial coding region for the RNA-dependent RNA polymerase (RdRp, 503 nucleotides) of these three samples suggested that two of them (B4836 and B4881) belong to genotype 2 (GIII.2) while the third one (B4848) was more closely related to genotype 1 (GIII.1) strains. By deep sequencing, the capsid region from two of these strains could be determined. This confirmed the circulation of genotype 1 (B4848) together with the presence of another sequence (B4881) sharing its highest genetic relatedness with genotype 1, but sufficiently distant to constitute a new genotype. This latter strain was shown in silico to be a recombinant: phylogenetic divergence was detected between its RNA-dependent RNA polymerase coding sequence (genotype GIII.2) and its capsid protein coding sequence (genotype GIII.1 or a potential norovirus genotype). According to this data, this strain could be the second genotype GIII.2_GIII.1 bovine norovirus recombinant described in literature worldwide. Further analysis suggested that this strain could even be a potential norovirus GIII genotype, tentatively named GIII.4. The data provides important epidemiological and evolutionary information on bovine noroviruses circulating in South America